Laboratory and patient of kyiv city clinical emergency hospital - O. B. Kryatchenko; V. P. Pechyborsch; V. M. Yakimets; S. I. Mazii; O. V. Pechyborsch; V. V. Yakimets; V. P. Maidanyuk; P. P. Yermuraki (Kazimierz Wielki University, 2021)
The aim of the work is to analyze the activities of the clinical diagnostic laboratory of the Kyiv City Clinical Emergency Hospital (hereinafter - KCCEH) in comparison with the hospitals of Kyiv for 2017-2018 and determine the role of existing mechanisms to optimize the activities of this laboratory. The article uses the materials of statistical reports of KCCEH and treatment and prevention facilities of Kyiv for 2017-2018 using the method of systematic analysis of statistical materials, as well as systemic and structural-functional approaches. Analysis of the main performance indicators of the clinical diagnostic laboratory of the Kyiv City Clinical Emergency Hospital shows that in 2018 compared to 2017 there is an increase of 2.9% in the absolute number of laboratory tests due to increased highly informative research and introduction of innovative technologies in diagnosis. In the context of reforming the health care system under the conditions of social and economic crisis and our country's hybrid war, the only most appropriate way to optimize the laboratory department of the Kyiv City Clinical Emergency Hospital and similar hospitals in Ukraine is the centralization of clinical laboratory research and laboratory services.